Al-Biruni Tuition Centre / Jenickson Juan … [et.al.]. - Juan, Jenickson; Merdicken, William Nichole; Abdul Wahab, Noraishah; Jaafar, Farizah Syahirah; Wan Zainal Abidin, Sharifah Aisah; Mading, Stephenie (2018)
Our company name is Al - Biruni Tuition Centre. The type of the business form is partnership in which it consists of 5 partners. Each of us will contribute the capital to the business based on the agreement that we have made. Our main focus of the business is .teaching and helping all the primary school students especially that are having big exams such as the Ujian Pencapaian Sekolah Rendah (UPSR). All the five of us have agreed to participate in the business management that we will establish are Jennickson Juan as our General Manager, Noraishah binti Abdul Wahab as Administration Manager, Farizah Syahirah binti Jaafar as the Financial Manager, Stephenie Anak Mading and William Nichole as Marketing Plan and lastly Sharifah Aisah as Operation Manager. Al - Biruni Tuition Centre is a company that we will teach basic learning and skills on how to answer during exams of all subjects. Our target customer is children that are from primary school which live in Samarahan area especially Desa Ilmu. This is because there are some school that are near the tuition centre such as Sekolah Kebangsaan Dato Mohammad Musa, Sekolah Kebangsaan Meranek, Sekolah Kebangsaan Dato Traoh Muara Tuang and many more